(untitled) (Colloquia Comparativa Litterarum, 2025)
The core topic of this paper is Marguerite Yourcenar’s translation (1937) of Virginia Woolf’s novel The Waves. I also trace back the major debate in France in 1993 when a second translation of The Waves by Cécile Wajsbrot appeared in French. In conclusion, the paper provides Marguerite Yourcenar’s reflection on Virginia Woolf. By outlining the genealogy of Marguerite Yourcenar’s writing, it goes beyond the obvious predecessors like Marcel Proust and Thomas Mann, in order to unmask Woolf as a possible precursor.